Pick-Up Strategy in Increasing Customer Attraction to Save at PT BPRS Mitra Harmoni Malang City - Nurwakhidah, Ana; Anam, Hoirul; Muhammad, Aliyu Dahiru (Malacca: Journal of Management and Business Development, 2025)
This study discusses the implementation of the pick-up strategy by PT BPRS Mitra Harmoni Kota Malang in increasing interest and number of customers, especially among traders and MSMEs. This strategy involves a direct and personalized approach through market promotions, visits to business locations, and door-to-door methods, which have proven to be effective in strengthening relationships and facilitating access to services to the community. In addition, banks implement pick-up promotional services that allow people to make transactions such as payments and deposits without having to come to the bank directly, thus saving time and costs. The system is equipped with features such as passbooks and deposit slips to support the supervision of customer funds and increase trust. Despite challenges such as competition from other financial institutions and a lack of understanding of the product by potential customers, this strategy has shown positive results in expanding service access, increasing satisfaction, and strengthening relationships with customers.   sfdfsdfed